Association between the triglyceride-glucose index and contrast-induced nephropathy in chronic total occlusion patients undergoing percutaneous coronary intervention - Serdar Söner; Adem Aktan; Raif Kılıç; Hamdullah Güzel; Ercan Taştan; Metin Okşul; Adnan Duha Cömert; Mehmet Sait Coşkun; Hülya Tosun Söner; Tuncay Güzel (BMC Cardiovascular Disorders)
Abstract Objective The triglyceride glucose (TyG) index is a biomarker of insulin resistance and is associated with an increased risk of cardiovascular events. Contrast-induced nephropathy (CIN) is an important complication that causes poor outcomes in patients undergoing percutaneous coronary intervention (PCI). In this study, we aimed to investigate the relationship between the TyG index and CIN and mortality in patients who underwent PCI due to chronic total coronary occlusion (CTO). Methods Two hundred eighteen individuals from three separate medical centers who underwent procedural PCI between February 2010 and April 2012 and had a CTO lesion in at least one coronary artery were recruited. According to the TyG index, patients were divided into two groups. Patients with a TyG index ≥ 8.65 were included in Group 1, and patients with a TyG index < 8.65 were included in Group 2. Patients were followed up for 96 months. The main outcome was the development of CIN and mortality. Results The mean age of the patients (65.8 ± 10.94 vs. 61.68 ± 11.4, P = 0.009), diabetes mellitus (60 [44.8%] vs. 11 [13.1%], P < 0.001), and dyslipidemia rates (52 [38.8%] vs. 21 [25%], P = 0.036) were higher in group 1. In multivariable logistic regression analysis, it was seen that age (OR = 1.04, 95% CI = 1.01–1.08, P = 0.020), chronic kidney disease (OR = 2.34, 95% CI = 1.02–5.33, P = 0.044), peripheral artery disease (OR = 5.66, 95% CI = 1.24–25.91, p = 0.026), LVEF (OR = 0.95, 95% CI = 0.92–0.99, P = 0.005), LDL cholesterol levels (OR = 1.00, 95%CI = 1.00–1.02, P = 0.024) and TyG index (OR = 2.17, 95% CI = 1.21–3.89, P = 0.009) were independent predictors of the development of CIN. Conclusion Our study demonstrates a correlation between the TyG index and the prevalence of CIN in patients with CTO undergoing PCI. Adding the TyG index to the routine clinical evaluation of patients with CTO undergoing PCI may help protect patients from the development of CIN. Graphical Abstract